Innovation Factors Influencing Performance Of Manufacturing SMEs In Malaysia - Othman, Aman (UTeM, 2014)
Innovation is a catalyst for the growth and development a country’s economy. The ever changing and uncertainty of the global economy has demanded Malaysia to emphasis on innovation and creativity as the key factors for a sustainable growth in the world of business. In this respect, the Small and Medium Enterprises (SMEs) which are recognized as the backbone of the nation’s economic growth need to be innovative and creative in order to be sustainable. However, some SMEs in Malaysia do not recognize change and reform as an innovation, and they do not consider innovation as part of their manufacturing activities. Further, despite their significant contributions to the Malaysian economy, the SMEs have not been given adequate attention in comparison to the larger size companies and public-listed enterprises in Malaysia. Hence, this study aims to investigate the innovation factors that influence the performance of Manufacturing SMEs in Malaysia. This study is an exploratory descriptive study that utilizes questionnaire as its main instrument for data collection. It was designed to identify and explore the influence of innovation factors in optimizing the business performance of the SMEs in Malaysia. 180 respondents representing the SMEs manufacturing sector in the Klang Valley and Southern Region Malaysia (Selangor, Wilayah Persekutuan, Negeri Sembilan, Melaka, and Johor Bahru) were involved in this study. The data were analyzed using the Statistical Package for Social Sciences (SPSS) version 16.0. The overall findings showed that all of the factors that contribute to the encouragement of innovation influence the business performance of the SMEs. Therefore, efforts towards imparting innovation should be prioritized in the SMEs in order to enhance their business operation. By doing so, they can be more effective and efficient so that they can contribute significantly towards the development of the national economy.